2015
DOI: 10.1590/s0102-865020150070000009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid on-site cytopathological examination (ROSE) performed by endosonagraphers and its improvement in the diagnosis of pancreatic solid lesions

Abstract: PURPOSE:To evaluate the diagnosis improvement of EUS-FNA when using ROSE performed by the endosonographer. METHODS:A retrospective study was conducted. A total of 48 pancreatic solid masses EUS-FNA were divided into two groups according to the availability of on-site cytology (ROSE) -the first 24 patients (group A-without ROSE) and the latter 24 cases (group B-with ROSE). Sensitivity, specificity, positive predictive value, negative predictive value, accuracy, complications and inadequacy rate of EUS-FNA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…A total of 1299 individuals were included, in which 3 studies enrolled over 200 individuals[ 8 , 10 , 15 ], 3 studies enrolled 100–200 individuals[ 9 , 21 , 22 ], and the other one study enrolled <100 individuals[ 16 ]. Of the 7 studies, one was randomized trial [ 15 ] and the other six were non-randomized comparative studies [ 8 10 , 16 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1299 individuals were included, in which 3 studies enrolled over 200 individuals[ 8 , 10 , 15 ], 3 studies enrolled 100–200 individuals[ 9 , 21 , 22 ], and the other one study enrolled <100 individuals[ 16 ]. Of the 7 studies, one was randomized trial [ 15 ] and the other six were non-randomized comparative studies [ 8 10 , 16 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analyses revealed that on-site cytopathology evaluation could improve diagnostic adequacy and accuracy for malignancy detection [ 12 14 ]. However, new and high quality studies published recently reported convertible conclusions [ 15 , 16 ]. Design inadequacies of previous meta-analysis limited their capacity in completely addressing this clinical question and left the benefits of ROSE remained controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown improved diagnostic yield and accuracy with ROSE [18][19][20]; however, more recent observational data on the impact of ROSE have yielded conflicting results [10,21]. A meta-analysis and systematic review by Kong et al showed that the use of ROSE did not improve the diagnostic yield and accuracy, nor did it improve the pooled sensitivity and specificity for EUS-FNA of pancreatic masses [22].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal endosonographers, confronted with the above-mentioned problem, have endeavored to evaluate the possibility of performing the on-site review of EUS-derived samples themselves since 2007 [25]. Although encouraging results have been presented in some studies, these have been conducted almost exclusively on patients undergoing investigation for pancreatic solid masses rather than for lymphadenopathy [25-28]. …”
Section: Discussionmentioning
confidence: 99%